2003
DOI: 10.1111/j.0014-3820.2003.tb00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Models of Speciation: What Have We Learned in 40 Years?

Abstract: Abstract. Theoretical studies of speciation have been dominated by numerical simulations aiming to demonstrate that speciation in a certain scenario may occur. What is needed now is a shift in focus to identifying more general rules and patterns in the dynamics of speciation. The crucial step in achieving this goal is the development of simple and general dynamical models that can be studied not only numerically but analytically as well. I review some of the existing analytical results on speciation. I first s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
433
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 486 publications
(453 citation statements)
references
References 86 publications
11
433
2
7
Order By: Relevance
“…These controversies have attracted the attention of many theoreticians, and by now the great majority of theoretical work on speciation concerns speciation in the presence of gene flow between diverging populations driven by ecological selection (Gavrilets 2004;Kirkpatrick and Ravigné 2002). Most of this work is represented by numerical studies, but there now exist a number of simple analytical models of sympatric speciation (Gavrilets 2003b(Gavrilets , 2004(Gavrilets , 2006Gavrilets and Waxman 2002). The theory of sympatric speciation is arguably the most developed part of theoretical speciation research.…”
Section: Modern Speciation Theorymentioning
confidence: 99%
“…These controversies have attracted the attention of many theoreticians, and by now the great majority of theoretical work on speciation concerns speciation in the presence of gene flow between diverging populations driven by ecological selection (Gavrilets 2004;Kirkpatrick and Ravigné 2002). Most of this work is represented by numerical studies, but there now exist a number of simple analytical models of sympatric speciation (Gavrilets 2003b(Gavrilets , 2004(Gavrilets , 2006Gavrilets and Waxman 2002). The theory of sympatric speciation is arguably the most developed part of theoretical speciation research.…”
Section: Modern Speciation Theorymentioning
confidence: 99%
“…Theoretical models have shown that, when it is associated with disruptive selection, assortative mating by single traits or multiple ecologically related traits facilitates sympatric speciation (Bolnick & Fitzpatrick, 2007; Dieckmann & Doebeli, 1999; Gavrilets, 2003) and local adaptation (Jiang et al., 2013). In a Tilapia species complex in the early stages of speciation, there was strong assortative mating by diet and color, which may promote species differentiation (Martin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Natural populations are rarely panmictic, and crucial consequences of spatial subdivision are (1) random genetic drift including historical factors, (2) uniform selection acting on separate subpopulations experiencing similar selection regimes, and (3) divergent selection acting on separate subpopulations living in different ecological environments. Each of these consequences may result in geographic variation and eventually reproductive isolation, but their relative importance in speciation is still unclear and probably case dependent (Coyne & Orr, 2004; Dieckmann, Doebeli, Metz, & Tautz, 2004; Gavrilet, 2003; Schluter, 2000, 2009). …”
Section: Introductionmentioning
confidence: 99%